(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
The Medical Certification of Cause of Death (MCCD) is a critical document serving legal, statistical, and public health purposes by recording the medically certified cause of death. However, certifying deaths becomes particularly challeng ing when individuals are “brought in dead” (BID) or declared “dead on arrival” (DOA) at hospitals. In such cases, the absence of prior medical history and unclear circumstances make it inappropriate for primary practitioners to issue MCCD without further evaluation. Certifying such deaths carries legal and ethical implications, especially in suspected unnatural deaths, where police inquests and post-mortem examinations under BNSS Section 194 are required. As per the Registration of Births and Deaths Act, 1969 [Section 10(2) & (3)], only registered medical practitioners who attended the patient during terminal illness are authorized to issue death certificates. As per National Medical Commission guide lines (Professional Conduct, Etiquette and Ethics Regulations, 2002) personal examination of the body before certifi cation is mandatory. Despite its importance, MCCD coverage and quality in India remain inadequate, averaging only 20%. Common deficiencies include incomplete, incorrect, or illegible entries. Strengthening hospital protocols, involving forensic experts, and providing regular training to medical staff are essential tools to improve accuracy. Additionally, establishing audit committees to review MCCD documentation can enhance accountability. Improving awareness and adherence to existing guidelines will enable MCCD to function more effectively as a tool for justice, health surveillance, and public policy.